Classification methods for remotely sensed data - Kavzoglu, Taskin; Tso, Brandt; Mather, Paul M. (CRC Press, 2025)
"The third edition of the bestselling Classification Methods for Remotely Sensed Data covers recent developments in the optimization of existing and new algorithms and presents new analysis tools and metrics together with ongoing debates on accuracy assessment strategies and metrics that did not exist 10 years ago. It is thoroughly updated and provides four new chapters on object-based image analysis, a new paradigm in image processing and classification. In object-based image analysis, hyperparameter optimization techniques are used to ensure that the highest possible accuracy is achieved by the algorithm"--
Revised edition of: Classification methods for remotely sensed data / Brandt Tso, Paul M. Mather. 2nd ed. 2009. - Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Remote sensing; Pattern recognition systems; Télédétection; Reconnaissance des formes (Informatique); remote sensing; TECHNOLOGY / Remote Sensing; TECHNOLOGY / Imaging Systems; SCIENCE / Earth Sciences / General